Mekanisme Terjadinya Hiperbilirubinemia pada Bayi Berat Lahir Rendah - Grasia P. Gerungan; Rocky Wilar; Max F. J. Mantik (Universitas Sam Ratulangi, 2023)
Abstract: Hyperbilirubinemia is frequently found in newborns, especially in low birth weight (LBW) infants (less than 2,500 g). Hyperbilirubinemia is an increase in bilirubin higher than 5 mg/dL which clinically manifests as icterus. This study aimed to evaluate the relationship between LBW and the incidence of hyperbilirubinemia as well as the underlying mechanism. This was a literature study. Article searching used databases of Pubmed and Google Schoolar and the keywords were Hyperbilirubinemia AND Low birth weight NAD Neonatal Jaundice. The results showed a relationship between LBW and the incidence of hyperbilirubinemia. There were increases of hemoglobin, heme catabolism, and destruction of bilirubin due to liver immaturity, impaired liver function and perfusion and bilirubin conjugation ability, less of albumin as the transportation protein and uridine diphosphate glucuronyltransferase (UDP-GT) to convert indirect bilirubin to direct bilirubin in the liver. In conclusion, there is a relationship between low birth weight and hyperbilirubinemia that occurs due to liver immaturity, impaired liver function and perfusion, and less of albumin and UDP-GT enzyme. Keywords: hyperbilirubinemia; low birth weight; neonatal jaundice Abstrak: Hiperbilirubinemia merupakan masalah yang sering terjadi pada bayi baru lahir terlebih bayi dengan berat lahir rendah (<2.500 gram). Hiperbilirubinemia merupakan peningkatan kadar bilirubin serum >5mg/dL yang bermanifestasi klinis berupa ikterus. Penelitian ini bertujuan untuk mengetahui hubungan antara BBLR dengan kejadian hiperbilirubinemia dan mekanisme terjadinya. Jenis penelitian ialah suatu literature review. Pencarian artikel menggunakan Pubmed dan Google Schoolar dengan kata kunci Hyperbilirubinemia AND Low birth weight AND Neonatal Jaundice. Hasil penelitian mendapatkan adanya hubungan antara BBLR dengan kejadian hiperbilirubinemia. Terdapat peningkatan jumlah hemoglobin, katabolisme heme dan penghan-curan bilirubin yang terjadi antara lain karena imaturitas hati yang belum optimal mengkonju-gasikan bilirubin, terganggunya fungsi dan perfusi hati serta kemampuan mengkonjugasi bilirubin, rendahnya kadar protein albumin sebagai transportasi dan enzim uridin difosfat glukoronid transferase (UDP-GT) untuk mengonversi bilirubin indirek menjadi bilirubin direk di dalam hati. Simpulan penelitian ini ialah terdapat hubungan antara BBLR dengan hiperbilirubinemia yang dapat terjadi karena imaturitas hati, terganggunya fungsi dan perfusi hati, serta kurangnya protein albumin dan enzim UDP-GT. Kata kunci: hiperbilirubinemia; low birth weight; neonatal jaundice